2021
DOI: 10.3390/ijms222111611
|View full text |Cite
|
Sign up to set email alerts
|

Reduced GFAP Expression in Bergmann Glial Cells in the Cerebellum of Sigma-1 Receptor Knockout Mice Determines the Neurobehavioral Outcomes after Traumatic Brain Injury

Abstract: Neuroprotective effects of Sigma-1 receptor (S1R) ligands have been observed in multiple animal models of neurodegenerative diseases. Traumatic brain injury (TBI)-related neurodegeneration can induce long-lasting physical, cognitive, and behavioral disabilities. The aim of our study was to evaluate the role of S1R in the development of neurological deficits after TBI. Adult male wild-type CD-1 (WT) and S1R knockout (S1R-/-) mice were subjected to lateral fluid percussion injury, and behavioral and histological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 59 publications
2
6
0
Order By: Relevance
“…The metabolomic study showed that the serotonin concentration was increased in the plasma and brains of Sig1R KO mice, which was associated with reduced behavioral despair. This is in agreement with our previous study, in which CD-1 Sig1R KO mice did not develop depression-like behavior after traumatic brain injury during the 1-year follow-up monitoring [ 25 ]. Previous studies reported that C57BL/6J background Sig1R KO male mice exhibited a depressive-like phenotype [ 19 , 20 , 21 , 23 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The metabolomic study showed that the serotonin concentration was increased in the plasma and brains of Sig1R KO mice, which was associated with reduced behavioral despair. This is in agreement with our previous study, in which CD-1 Sig1R KO mice did not develop depression-like behavior after traumatic brain injury during the 1-year follow-up monitoring [ 25 ]. Previous studies reported that C57BL/6J background Sig1R KO male mice exhibited a depressive-like phenotype [ 19 , 20 , 21 , 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…The tail suspension test was performed at 2, 6, and 15 months of age to detect a depressive state in mice as described previously [ 25 , 32 ]. To prevent tail climbing behavior, a plastic tube (4 cm long) was put on each mouse’s tail.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These data are consistent with recently published results in mice suffering from progressive and severe depression-like behavior 6 months after CCI (16). Our previous findings revealed that moderate latFPI also induces depressive-like behavior in male CD-1 mice (21). However, there are also reports where depression-like behavior is not observed within 12 months after closed head injury (46).…”
Section: Discussionsupporting
confidence: 93%